Bioethical and legal problems in euthanasia - Onwujekwe Udodi E; Gerasimchuk, Nina (My University, 2015)
Euthanasia is the intentional and painless taking of the life of another person, by act or omission, for compassionate motives. The word euthanasia is derived from the Ancient Greek language and can be literally interpreted as ‘good death.’
Keywords: euthanasia; good death